Experiences and lessons learned from interventions in the Lake Victoria Basin: The Lake Victoria Environmental Management Project - Muyodi, Fredrick J.; Bugenyi, Fredrick W. B.; Hecky, Robert E. (Lakes & Reservoirs: Research & Management, 2010)
The Lake Victoria basin has experienced a myriad of environmental changes leading to its degradation, and necessitating various interventions to be implemented. The purpose of this study was to review early development initiatives, past and ongoing interventions in order to document experiences and lessons learned from them. The methods used in this study include review of published articles, project reports, and personal opinions of experts and project implementers in the lake basin. There are numerous threats to the lake basin, the major ones being poor land use and agricultural practices, catchment deforestation, destruction of wetlands, pollution loading, fishing malpractices and invasion by exotic aquatic weeds. These threats have resulted in rampant land and wetland degradation, leading to poor water quality and consequent water loss, a decline in the diversity of the commercial fisheries, and the lake’s biodiversity in general, unsustainable use of natural resources, increased poor human health and food insecurity, with high levels of poverty among the riparian communities. Initiatives for socio-economic development within the lake basin began as early as the turn of the 20th century, while intervention studies started as early as the 1920s. Current lake management intervention projects, such as the Lake Victoria Environmental Management Project (LVEMP), undertaken by the riparian states of the East African Community, have invested heavily in the lake basin, with the goal of addressing the above-noted threats to the lake. Some pilot projects undertaken through the LVEMP include: (i) water quality and quantity monitoring; (ii) industrial and municipal management; (iii) fisheries studies; (iv) water hyacinth control; (v) wetlands; (vi) land use; (vii) catchment afforestation; and (viii) micro-projects to alleviate poverty, to cite a few examples. Phase 1 of the LVEMP was a major effort in the history of the lake basin; hence, its critical examination. To this end, this study highlights, in chronological order, the experiences, achievements, challenges and lessons learned with regard to Phase 1 of the LVEMP.
Keywords: Aquatic weeds; Environmental degradation; Fisheries production; Lake Victoria; LVEMP; Management interventions; Socio-economic; Water quality